Using Visual, Linguistic and Sensory Prompts in Fostering Meaningful Writing Processes with Teenagers in a Public School (2022)
ABSTRACT: This action research project reports how the use of multimodal resources in the English class fosters meaningful writing processes with a group of teenagers from a public school in Medellín, Colombia. Collection of data was done through class observations, a focus group, an in-depth interview, and students ́ written works. The implementation of some cycles, in which the emphasis was on using different modalities of prompts to foster students’ meaningful writing evidenced that students developed a sense of enjoyment related to the connection of writing withtheir life experiences and self-knowledge; in addition to this, meaningful construction considering the awareness of stages in their writing processes enhanced confidence in themselves and with the teacher.